Composites, shaped bodies and electronic components

By using characteristic composites, the thermal expansion coefficient and mechanical properties of the cured substances in the range of 25°C to 250°C meet specific conditions, solving the problem that the molded body is prone to cracks during heating, and achieving higher mechanical strength and heat resistance.

CN112166155BActive Publication Date: 2025-03-07RESONAC CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN201880093822.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2018-05-31
Publication Date
2025-03-07
Estimated Expiration
2038-05-31

AI Technical Summary

Technical Problem

In the case of industrial products made from composites, after the composite and the metal member are closely combined and cured, cracks are easily formed during the heating process, mainly due to the difference in thermal expansion coefficients between the cured compound of the composite and the metal member.

Method used

A composite with a specific coefficient of thermal expansion and mechanical properties is adopted. The glass transition temperature (Tg) of the cured product is above 25°C and less than 250°C, and the coefficient of thermal expansion (CTE1 and CTE2) in the range of 25°C to 250°C and the flexural elastic modulus (E) and flexural strength (σ) at 250°C are used. The stress index (SI) and fracture index (FI) defined by these characteristics are above 0 and below 150 to ensure that the composite reduces stress during heating and inhibits the formation of cracks.

Benefits of technology

By using such a characteristic composite, cracks in the molded body made of the composite and metal components can be effectively suppressed, the mechanical strength and heat resistance of the molded body can be improved, and the service life can be extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure BDA0002798838120000101
    Figure BDA0002798838120000101
Patent Text Reader

Abstract

This invention provides a composite that suppresses cracking in molded articles made from the composite and metal components. The composite comprises a powder containing a metal element and a resin composition. The glass transition temperature of the cured composite is denoted as Tg [°C]. The coefficient of thermal expansion of the cured composite at 25°C or higher and lower than Tg°C is denoted as CTE1 [ppm / °C]. The coefficient of thermal expansion of the cured composite at 250°C or higher is denoted as CTE2 [ppm / °C]. The flexural modulus of the cured composite at 250°C is denoted as E [GPa]. The flexural strength of the cured composite at 250°C is denoted as σ [MPa]. The stress index SI of the cured composite, defined by the following formula (I), is 0 or higher and 150 or lower: SI=|[CTE1×(Tg-25)+CTE2×(250-Tg)-17×(250-25)]×E / σ|(I).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composite, a shaped body and an electronic component. Background Art

[0002] A composite material including a metal powder and a resin composition is used as a raw material for various industrial products such as inductors, electromagnetic shielding materials, and bonded magnets, depending on the physical properties of the metal powder (see Patent Document 1 below).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2014-13803 Summary of the invention

[0006] Problems to be solved by the invention

[0007] When manufacturing industrial products from composites, the composite and the metal component are brought into close contact and the composite is cured to produce a molded body, and then the molded body is sometimes heated. During the heating process of the molded body, cracks are easily formed in the molded body due to the difference in thermal expansion coefficient between the cured composite and the metal component.

[0008] The present invention has been made in view of the above circumstances, and an object thereof is to provide a composite capable of suppressing cracks in a molded body made of a composite and a metal member, a molded body including a cured product of the composite, and an electronic component including a cured product of the composite.

[0009] Means for solving problems

[0010] A composite material according to one aspect of the present invention is a composite material comprising a powder containing a metal element and a resin composition, wherein the glass transition temperature of a cured product of the composite material is represented by Tg [°C], the thermal expansion coefficient of the cured product of the composite material at a temperature of 25°C or higher and less than Tg°C is represented by CTE1 [ppm / °C], the thermal expansion coefficient of the cured product of the composite material at a temperature of 25°C or higher and less than 250°C is represented by CTE2 [ppm / °C], the bending elastic modulus of the cured product of the composite material at 250°C is represented by E [GPa], the bending strength of the cured product of the composite material at 250°C is represented by σ [MPa], and the stress index SI (Stress Index) of the cured product of the composite material defined by the following formula (I) is greater than 0 and less than 150.

[0011] SI=|[CTE1×(Tg-25)+CTE2×(250-Tg)-17×(250-25)]×E / σ|(I)

[0012] In the composite according to one aspect of the present invention, the flexural elongation of the cured composite at 250° C. can be expressed as ε [%], and the fracture index FI (Fracture Index) defined by the following formula (II) can be 3.0 MPa to 10.0 MPa.

[0013] FI=ε×σ / 2 (II)

[0014] In the composite according to one aspect of the present invention, the content of the powder containing the metal element may be 90% by mass or more and less than 100% by mass.

[0015] A molded body according to one aspect of the present invention includes a cured product of the above-mentioned composite.

[0016] An electronic component according to one aspect of the present invention includes a cured product of the above-mentioned composite material and an element covered with the cured product of the composite material, wherein the element has a metal member.

[0017] Effects of the Invention

[0018] According to the present invention, there are provided a composite capable of suppressing cracks in a molded body made of a composite and a metal member, a molded body including a cured product of the composite, and an electronic component including a cured product of the composite. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 : is a schematic diagram which shows the method of a bending test, and is a schematic side view of a bending test jig and a test piece.

[0020] Figure 2 (a) is a schematic cross-sectional view of an electronic component according to an embodiment of the present invention, Figure 2 (b) is a schematic cross-sectional view of an electronic component according to another embodiment of the present invention.

[0021] Figure 3 This is a schematic cross-sectional view of an electronic circuit board according to one embodiment of the present invention. DETAILED DESCRIPTION

[0022] Hereinafter, preferred embodiments of the present invention will be described, but the present invention is not limited to the following embodiments.

[0023] <Overview of the compound>

[0024] The composite material involved in this embodiment comprises a powder containing a metal element and a resin composition. The glass transition temperature of the cured material of the composite material is represented by Tg [°C]. The thermal expansion coefficient of the cured material of the composite material at a temperature above 25°C and below Tg°C is represented by CTE1 [ppm / °C]. The thermal expansion coefficient of the cured material of the composite material at a temperature above Tg°C and below 250°C is represented by CTE2 [ppm / °C]. The bending modulus of the cured material of the composite material at 250°C is represented by E [GPa]. The bending strength of the cured material of the composite material at 250°C is represented by σ [MPa]. The stress index SI of the cured material of the composite material defined by the following formula (I) is greater than 0 and less than 150.

[0025] SI=|[CTE1×(Tg-25)+CTE2×(250-Tg)-17×(250-25)]×E / σ|(I)

[0026] In the case of manufacturing industrial products from a composite, the composite is made to fit tightly with a metal component, and the composite is cured to produce a molded body, after which the molded body is sometimes heated. In the process of heating a molded body formed from a conventional composite, cracks are easily formed in the molded body due to the difference in thermal expansion coefficient between the cured product of the composite and the metal component. For example, when an inductor is made by sealing a coil with a cured product of a composite and mounting the inductor on an electronic circuit substrate, a reflow soldering process (soldering) is performed to connect the inductor and the electronic circuit substrate. In the reflow soldering process, the inductor is heated in a state where the cured product of the composite is in close contact with the coil. In the process of heating a conventional inductor, cracks are easily formed in the inductor due to the difference in thermal expansion coefficient between the cured product of the composite and the coil. Cracks are easily formed on the inner side of the coil. If cracks are formed in the inductor, the inductance of the inductor is reduced. Cracks cannot be fully suppressed simply by reducing the difference in thermal expansion coefficient between the cured product of the conventional composite and the metal component. The present inventors have found that cracks caused by the difference in thermal expansion coefficient between a cured product of the composite and a metal member can be suppressed by using a composite having a stress index SI of 0 or more and 150 or less as defined by the above formula (I).

[0027] [CTE1×(Tg-25)+CTE2×(250-Tg)-17×(250-25)] in the formula (I) can be replaced by the difference D in expansion between the cured product of the composite and the metal component (such as copper) at a temperature above 25°C and below 250°C. That is, the SI defined by the above formula (I) can be expressed as D×E / σ. The smaller D is, the smaller the SI is, and the more difficult it is to form cracks. The smaller the above bending modulus E is, the smaller the SI is, and the more difficult it is to form cracks. The larger the above bending strength σ is, the smaller the SI is, and the more difficult it is to form cracks. By making the SI greater than 0 and less than 150, the stress acting on the formed body is sufficiently reduced as the temperature of the formed body changes, thereby suppressing cracks in the formed body. The upper limit value of SI of 150 was first discovered through research by the inventors of the present invention. However, the effects of the present invention are not limited to the above matters. SI can be freely adjusted by the composition and amount of the powder containing the metal element contained in the composite, the composition and amount of the resin composition, and the like.

[0028] The stress index SI may be 0 to 140, 0 to 135, 0 to 130, 0 to 100, or 0 to 70. When the SI is within the above range, cracks in a molded body formed of the composite are easily suppressed.

[0029] The bending elongation of the cured product of the composite at 250°C is expressed as ε[%]. The fracture index FI defined by the following formula (II) can be greater than 3.0 MPa and less than 10.0 MPa, or greater than 4 MPa and less than 9.0 MPa. FI is a numerical value represented by the product of bending strength (MPa) and bending elongation (%). When FI is within the above range, cracks in the molded body formed by the composite are easily suppressed. FI can be freely adjusted by the composition and amount of the powder containing the metal element contained in the composite, the composition and amount of the resin composition, etc.

[0030] FI=ε×σ / 2 (II)

[0031] The powder containing metal elements is composed of a plurality (a large number) of particles containing metal elements. The powder containing metal elements (particles containing metal elements) may contain, for example, at least one selected from a metal element, an alloy and a metal compound. The resin composition contains at least a resin. For example, the resin composition may contain an epoxy resin. The resin composition may contain other components in addition to the resin. For example, the resin composition may contain a compound (chemical compound) having a siloxane bond. Compounds having a siloxane bond are sometimes referred to as "siloxane compounds". The resin composition may contain a curing agent. The resin composition may also contain a curing accelerator. The resin composition may contain additives. The resin composition is a component that may include resin, siloxane compound, curing agent, curing accelerator and additives, or may be the remaining components (non-volatile components) except for organic solvents and powder containing metal elements. Additives refer to the remaining components in the resin composition except for resin, siloxane compound, curing agent and curing accelerator. Additives are, for example, coupling agents or flame retardants. The resin composition may contain wax as an additive. The composite may be a powder (composite powder).

[0032] The composite may include a powder containing a metal element, and a resin composition attached to the surface of each metal-containing particle constituting the powder containing the metal element. The resin composition may cover the entire surface of the particle, or may only cover a portion of the surface of the particle. The composite may include an uncured resin composition and a powder containing a metal element. The composite may also include a semi-cured product of a resin composition (e.g., a B-stage resin composition) and a powder containing a metal element. The composite may also include both an uncured resin composition and a semi-cured product of a resin composition. The composite may be composed of a powder containing a metal element and a resin composition.

[0033] In order to easily adjust SI and FI within the above range, the content of the powder containing metal elements in the composite can be 90 mass% or more and less than 100 mass%, 90 mass% or more and 99.8 mass% or less, 92 mass% or more and 99.8 mass% or less, relative to the mass of the entire composite. The composite may contain other fillers (e.g., silica fillers) in addition to the powder containing metal elements.

[0034] In order to easily adjust SI and FI within the above range, the content of the resin composition in the composite can be greater than 0.2 mass % and less than 10 mass %, or greater than 4 mass % and less than 6 mass % relative to the mass of the entire composite (for example, the total mass of the powder containing the metal element and the resin composition).

[0035] The average particle size of the metal element-containing powder is not particularly limited, and may be, for example, 1 μm or more and 300 μm or less. The average particle size can be measured, for example, using a particle size distribution meter. The shape of each metal element-containing particle constituting the metal element-containing powder is not limited, and may be, for example, spherical, flat, prism-shaped, or needle-shaped. The composite may include a plurality of metal element-containing powders having different average particle sizes.

[0036] According to the composition or combination of the powder containing metal elements contained in the composite, the various properties such as the electromagnetic properties of the molded body formed by the composite can be freely controlled, and the molded body can be used in various industrial products or their raw materials. Industrial products manufactured using composites can be, for example, automobiles, medical equipment, electronic equipment, electrical equipment, information and communication equipment, home appliances, audio equipment, and general industrial equipment. For example, in the case where the composite contains permanent magnets such as Sm-Fe-N alloys or Nd-Fe-B alloys as powders containing metal elements, the composite can be used as a raw material for bonded magnets. In the case where the composite contains soft magnetic powders such as Fe-Si-Cr alloys or ferrites as powders containing metal elements, the composite can be used as a raw material for an inductor (such as an EMI filter) or a transformer (such as a magnetic core or a sealing material). In the case where the composite contains iron and copper as powders containing metal elements, a molded body (such as a sheet) formed by the composite can be used as an electromagnetic wave shielding material.

[0037] <Composition of the compound>

[0038] (Resin composition)

[0039] The resin composition has the function of a binding material (binder) for the particles containing metal elements constituting the powder containing metal elements, and imparts mechanical strength to the molded body formed by the composite. For example, the resin composition is filled between the particles containing metal elements when the composite is molded under high pressure using a mold, and the particles containing metal elements are bonded to each other. By curing the resin composition in the molded body, the cured product of the resin composition more firmly bonds the particles containing metal elements to each other, and the mechanical strength of the molded body is improved.

[0040] The resin composition contains at least a resin. The resin composition may contain an epoxy resin as a thermosetting resin. By making the composite contain an epoxy resin having excellent fluidity among thermosetting resins, the fluidity, storage stability and formability of the composite are improved. However, as long as the effect of the present invention is not hindered, the composite may also contain other resins in addition to the epoxy resin. For example, the resin composition may contain at least one of a phenolic resin and a polyamide-imide resin as a thermosetting resin. In the case where the resin composition contains both an epoxy resin and a phenolic resin, the phenolic resin may function as a curing agent for the epoxy resin. The resin composition may contain a thermoplastic resin. For example, the thermoplastic resin may be at least one selected from acrylic resins, polyethylene, polypropylene, polystyrene, polyvinyl chloride and polyethylene terephthalate. The resin composition may contain both a thermosetting resin and a thermoplastic resin. The resin composition may contain a silicone resin.

[0041] The epoxy resin may be, for example, a resin having two or more epoxy groups in one molecule. The epoxy resin may be, for example, a biphenyl epoxy resin, a stilbene epoxy resin, a diphenylmethane epoxy resin, a sulfur-containing epoxy resin, a linear phenolic epoxy resin, a dicyclopentadiene epoxy resin, a salicylaldehyde epoxy resin, a copolymerized epoxy resin of naphthols and phenols, an epoxide of an aralkyl phenolic resin, a bisphenol epoxy resin, an epoxy resin containing a bisphenol skeleton, an alcohol glycidyl ether epoxy resin, a p-xylene and / or m-xylene modified phenolic resin glycidyl ether epoxy resin, a terpene modified phenolic resin glycidyl ether epoxy resin, At least one of ether-type epoxy resins, cyclopentadiene-type epoxy resins, glycidyl ether-type epoxy resins of polycyclic aromatic ring-modified phenolic resins, glycidyl ether-type epoxy resins of naphthalene-ring-containing phenolic resins, glycidyl ester-type epoxy resins, glycidyl or methylglycidyl-type epoxy resins, alicyclic epoxy resins, halogenated phenol linear phenolic epoxy resins, o-cresol linear phenolic epoxy resins, hydroquinone-type epoxy resins, trimethylolpropane-type epoxy resins, and linear aliphatic epoxy resins obtained by oxidizing olefin bonds with peracids such as peracetic acid.

[0042] From the viewpoint of excellent fluidity, the epoxy resin may be at least one selected from biphenyl epoxy resin, o-cresol novolac epoxy resin, phenol novolac epoxy resin, bisphenol epoxy resin, epoxy resin having a bisphenol skeleton, salicylaldehyde novolac epoxy resin and naphthol novolac epoxy resin.

[0043] The epoxy resin may be a crystalline epoxy resin. Although the molecular weight of the crystalline epoxy resin is relatively low, the crystalline epoxy resin has a relatively high melting point and excellent fluidity. The crystalline epoxy resin (highly crystalline epoxy resin) may be, for example, at least one selected from a hydroquinone epoxy resin, a bisphenol epoxy resin, a thioether epoxy resin, and a biphenyl epoxy resin. Commercially available products of crystalline epoxy resins may be selected from, for example, Epiclon 860, Epiclon 1050, Epiclon 1055, Epiclon 2050, Epiclon 3050, Epiclon 4050, Epiclon 7050, Epiclon HM-091, Epiclon HM-101, Epiclon N-730A, Epiclon N-740, Epiclon N-770, Epiclon N-775, Epiclon N-865, Epiclon HP-4032D, Epiclon HP-7200L, Epiclon HP-7200, Epiclon HP-7200H, Epiclon HP-7200HH, Epiclon HP-7200HHH, Epiclon HP-4700, Epiclon HP-4710, Epiclon HP-4770, Epiclon HP-5000, Epiclon HP-6000, N500P-2 and N500P-10 (these are trade names of DIC Corporation), NC-3000, NC-3000-L, NC-3000-H, NC-3100, CER-3000-L, NC-2000-L, XD-1000, NC-7000-L, NC-7300-L, EPPN-501H, EPPN-501HY, EPPN- At least one of 502H, EOCN-1020, EOCN-102S, EOCN-103S, EOCN-104S, CER-1020, EPPN-201, BREN-S, BREN-10S (all trade names manufactured by Nippon Kayaku Co., Ltd.), YX-4000, YX-4000H, YL4121H and YX-8800 (all trade names manufactured by Mitsubishi Chemical Corporation).

[0044] From the viewpoint of easily adjusting SI and FI to the above range and easily suppressing cracks in the molded body formed by the composite, the resin composition may contain at least one of a biphenylene aralkyl type epoxy resin and an isocyanate modified epoxy resin as the epoxy resin. The resin composition may also contain both a biphenylene aralkyl type epoxy resin and an isocyanate modified epoxy resin as the epoxy resin. A commercial product of a biphenylene aralkyl type epoxy resin may be, for example, NC-3000 manufactured by Nippon Kayaku Co., Ltd. A commercial product of an isocyanate modified epoxy resin may be, for example, AER-4001 manufactured by Asahi Kasei Corporation (formerly Asahi Kasei Electronic Materials Co., Ltd.).

[0045] The resin composition may contain one of the epoxy resins mentioned above. The resin composition may also contain multiple epoxy resins mentioned above.

[0046] Curing agents are classified into curing agents that cure epoxy resins in a range from low temperature to room temperature and heat-curing curing agents that cure epoxy resins by heating. Curing agents that cure epoxy resins in a range from low temperature to room temperature include, for example, aliphatic polyamines, polyaminoamides, and polythiol. Heat-curing curing agents include, for example, aromatic polyamines, acid anhydrides, phenol novolac resins, and dicyandiamide (DICY).

[0047] When using a curing agent that cures epoxy resin in a range from low temperature to room temperature, there is a tendency that the glass transition temperature of the cured product of epoxy resin is low and the cured product of epoxy resin is soft. As a result, the molded body formed by the composite is also easily softened. On the other hand, from the viewpoint of improving the heat resistance of the molded body, the curing agent may preferably be a heat-curing curing agent, may more preferably be a phenolic resin, and may further preferably be a phenolic novolac resin. In particular, by using a phenolic novolac resin as a curing agent, it is easy to obtain a cured product of epoxy resin with a high glass transition temperature. As a result, the heat resistance and mechanical strength of the molded body are easily improved.

[0048] Phenolic resin can be selected from at least one of aralkyl phenolic resin, dicyclopentadiene phenolic resin, salicylaldehyde phenolic resin, linear phenolic resin, copolymerized phenolic resin of benzaldehyde phenol and aralkyl phenol, p-xylene and / or m-xylene modified phenolic resin, melamine modified phenolic resin, terpene modified phenolic resin, dicyclopentadiene naphthol resin, cyclopentadiene modified phenolic resin, polycyclic aromatic ring modified phenolic resin, biphenyl phenolic resin and triphenylmethane phenolic resin. Phenolic resin can be a copolymer consisting of two or more of the above. As a commercially available product of phenolic resin, for example, Tamanol 758 made by Arakawa Chemical Industries, Ltd. or HP-850N made by Hitachi Chemical Co., Ltd. can be used.

[0049] The phenol novolac resin may be, for example, a resin obtained by condensing or co-condensing phenols and / or naphthols with aldehydes under an acidic catalyst. The phenols constituting the phenol novolac resin may be, for example, at least one of phenol, cresol, xylenol, resorcinol, catechol, bisphenol A, bisphenol F, phenylphenol, and aminophenol. The naphthols constituting the phenol novolac resin may be, for example, at least one selected from α-naphthol, β-naphthol, and dihydroxynaphthalene. The aldehydes constituting the phenol novolac resin may be, for example, at least one selected from formaldehyde, acetaldehyde, propionaldehyde, benzaldehyde, and salicylaldehyde.

[0050] The curing agent may be, for example, a compound having two phenolic hydroxyl groups in one molecule. The compound having two phenolic hydroxyl groups in one molecule may be, for example, at least one selected from resorcinol, catechol, bisphenol A, bisphenol F, and substituted or unsubstituted biphenols.

[0051] The resin composition may contain one of the phenolic resins mentioned above. The resin composition may also contain multiple phenolic resins mentioned above. The resin composition may contain one of the curing agents mentioned above. The resin composition may also contain multiple curing agents mentioned above.

[0052] The ratio of the active group (phenolic OH group) in the curing agent that reacts with the epoxy group in the epoxy resin is preferably 0.5 to 1.5 equivalents, more preferably 0.75 to 1.25 equivalents per 1 equivalent of the epoxy group in the epoxy resin. When the ratio of the active group in the curing agent is within the above range, the fluidity of the composite is easily improved.

[0053] The curing accelerator is not limited as long as it is a composition that reacts with the epoxy resin and promotes the curing of the epoxy resin. The curing accelerator can be, for example, an imidazole such as an alkyl-substituted imidazole or a benzimidazole. The resin composition can have a curing accelerator. The resin composition can also have a variety of curing accelerators. By making the resin composition contain a curing accelerator, the formability and demoulding properties of the composite are easily improved. In addition, by making the resin composition contain a curing accelerator, the mechanical strength of the molded body (such as an electronic component) manufactured using the composite is improved, or the storage stability of the composite under a high temperature and high humidity environment is improved. As commercially available imidazole curing accelerators, for example, at least one selected from 2MZ-H, C11Z, C17Z, 1,2DMZ, 2E4MZ, 2PZ-PW, 2P4MZ, 1B2MZ, 1B2PZ, 2MZ-CN, C11Z-CN, 2E4MZ-CN, 2PZ-CN, C11Z-CNS, 2P4MHZ, TPZ and SFZ (the above are product names manufactured by Shikoku Chemical Industry Co., Ltd.) can be used.

[0054] The amount of curing accelerator is not particularly limited as long as it is the amount that can obtain the curing acceleration effect. However, from the viewpoint of curability and fluidity when improving the moisture absorption of resin combination, the amount of curing accelerator relative to 100 mass parts of epoxy resin can be preferably more than 0.1 mass part and less than 30 mass parts, more preferably more than 1 mass part and less than 15 mass parts. The content of curing accelerator is preferably more than 0.001 mass part and less than 5 mass parts relative to the total 100 mass parts of the mass of epoxy resin and curing agent (such as phenolic resin). In the case where the amount of curing accelerator is less than 0.1 mass part, it is difficult to obtain sufficient curing acceleration effect. In the case where the amount of curing accelerator is greater than 30 mass parts, the storage stability of the composite is easily reduced. However, even if the amount of curing accelerator and content are the situation outside the above range, the effect of the present invention can also be obtained.

[0055] From the viewpoint of being easy to adjust SI and FI to the above range and to suppress cracks of the molded body formed by the composite, the resin composition may contain a compound having a siloxane bond (siloxane compound). A siloxane bond is a bond comprising two silicon atoms (Si) and one oxygen atom (O), which can be represented by -Si-O-Si-. The resin composition may contain one siloxane compound or a plurality of siloxane compounds. From the viewpoint of being easy to adjust SI and FI to the above range and to suppress cracks of the molded body formed by the composite, the resin composition preferably contains at least one of the first siloxane compound and the second siloxane compound described later as the siloxane compound. The resin composition may contain only the first siloxane compound as the siloxane compound, or may contain only the second siloxane compound as the siloxane compound. The resin composition may also contain both the first siloxane compound and the second siloxane compound. The resin composition may also contain siloxane compounds other than the first siloxane compound and the second siloxane compound. Hereinafter, the first siloxane compound and the second siloxane compound will be described in detail.

[0056] The first siloxane compound may have a structural unit represented by the following chemical formula (1). The structural unit represented by the following chemical formula (1) may be referred to as "structural unit 1".

[0057] [Chemistry 1]

[0058]

[0059] In the above chemical formula (1), R 1 and R 2Each of them is independently an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, a monovalent organic group having an epoxy group, a monovalent organic group having a carboxyl group, or a polyalkylene ether group having 3 to 500 carbon atoms.

[0060] The first siloxane compound may have a plurality of structural units 1. The plurality of R 1 The plurality of R present in the first siloxane compound may be the same as or different from each other. 2 They may be the same or different from each other. 1 and R 2 They may be the same as or different from each other. The first siloxane compound may have a repeating unit represented by the above chemical formula (1).

[0061] From the viewpoint of easily adjusting SI and FI within the above ranges and easily suppressing cracks in a molded body formed of the composite, the first siloxane compound preferably has a structural unit represented by the following chemical formula (2). The structural unit represented by the following chemical formula (2) is sometimes referred to as "structural unit 2".

[0062] [Chemistry 2]

[0063]

[0064] In the above chemical formula (2), R 3 It is an alkylene group having 1 to 10 carbon atoms.

[0065] The first siloxane compound may have a plurality of structural units 2. The plurality of R 3 They may be the same as or different from each other. The first siloxane compound may have a repeating unit represented by the above chemical formula (2).

[0066] The first siloxane compound is preferably a compound represented by the following chemical formula (3) from the viewpoint of being easy to adjust SI and FI to the above ranges and being easy to suppress cracks in a molded body formed of the composite. The compound represented by the following chemical formula (3) is sometimes referred to as "Compound 3".

[0067] [Chemistry 3]

[0068]

[0069] In the above chemical formula (3), n is an integer of 1 to 200. m1 and m2 are each independently an integer of 1 to 200. 4 , R 5 , R 6 and R 7Each of R is independently an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, a monovalent organic group having an epoxy group, a monovalent organic group having a carboxyl group, or a polyalkylene ether group having 3 to 500 carbon atoms. 8 and R 9 Each R is independently an alkylene group having 1 to 10 carbon atoms. 10 and R 11 Each independently is a divalent hydrocarbon group having 1 to 10 carbon atoms.

[0070] The presence of multiple R 4 The multiple R present in compound 3 may be the same or different. 5 can be the same as or different from each other. 4 , R 5 , R 6 and R 7 The multiple R present in compound 3 may be the same or different. 8 The multiple R present in compound 3 may be the same or different. 9 They may be the same or different from each other. 8 and R 9 The weight average molecular weight (Mw) of compound 3 may be, for example, 4,000 or more and 20,000 or less.

[0071] Commercially available products of Compound 3 include, for example, DBL-C31 and DBL-C32 manufactured by Gelest Corporation.

[0072] From the viewpoint of being easy to adjust SI and FI within the above range and being easy to suppress cracks in a molded body formed of the composite, the second siloxane compound preferably has a structural unit represented by the following chemical formula (4) and a structural unit represented by the following chemical formula (5). The structural unit represented by the following chemical formula (4) is sometimes referred to as "structural unit 4". The structural unit represented by the following chemical formula (5) is sometimes referred to as "structural unit 5".

[0073] [Chemistry 4]

[0074]

[0075] In the above chemical formula (4), R 12 It is a monovalent hydrocarbon group having 1 to 12 carbon atoms.

[0076] R 12For example, it may be an alkyl group such as methyl, ethyl, propyl, butyl, isopropyl, isobutyl, tert-butyl, pentyl, hexyl, heptyl, octyl, 2-ethylhexyl, etc.; an alkenyl group such as vinyl, allyl, butenyl, pentenyl, hexenyl, etc.; an aryl group such as phenyl, tolyl, xylyl, naphthyl, biphenyl, etc.; an aralkyl group such as benzyl, phenethyl, etc., etc. 12 Preferred is methyl or phenyl.

[0077] The second siloxane compound may have a plurality of structural units 4. 12 The second siloxane compound may have a repeating unit represented by the above chemical formula (4).

[0078] [Chemistry 5]

[0079]

[0080] In the above chemical formula (5), R 13 and R 14 Each independently is a monovalent hydrocarbon group having 1 to 12 carbon atoms.

[0081] R 13 For example, it may be an alkyl group such as methyl, ethyl, propyl, butyl, isopropyl, isobutyl, tert-butyl, pentyl, hexyl, heptyl, octyl, 2-ethylhexyl, etc.; an alkenyl group such as vinyl, allyl, butenyl, pentenyl, hexenyl, etc.; an aryl group such as phenyl, tolyl, xylyl, naphthyl, biphenyl, etc.; an aralkyl group such as benzyl, phenethyl, etc., etc. 13 Preferred is methyl or phenyl.

[0082] R 14 For example, it may be an alkyl group such as methyl, ethyl, propyl, butyl, isopropyl, isobutyl, tert-butyl, pentyl, hexyl, heptyl, octyl, 2-ethylhexyl, etc.; an alkenyl group such as vinyl, allyl, butenyl, pentenyl, hexenyl, etc.; an aryl group such as phenyl, tolyl, xylyl, naphthyl, biphenyl, etc.; an aralkyl group such as benzyl, phenethyl, etc., etc. 14 Preferred is methyl or phenyl.

[0083] The second siloxane compound may have a plurality of structural units 5. 13 The plurality of R present in the second siloxane compound may be the same as or different from each other. 14 can be the same as or different from each other. 13 and R 14 They may be the same as or different from each other. The second siloxane compound may have a repeating unit represented by the above chemical formula (5).

[0084] From the viewpoint of storage stability of the second siloxane compound, the molecular terminal of the second siloxane compound is preferably R12 , R 13 , R 14 The alkoxy group may be, for example, a methoxy group, an ethoxy group, a propoxy group or a butoxy group.

[0085] From the viewpoint of easily adjusting SI and FI within the above ranges and easily suppressing cracks in a molded body formed of the composite, the second siloxane compound preferably has a structural unit represented by the following chemical formula (6). The structural unit represented by the following chemical formula (6) is sometimes referred to as "structural unit 6".

[0086] [Chemistry 6]

[0087]

[0088] In the above chemical formula (6), R 15 It is a monovalent hydrocarbon group having 1 to 12 carbon atoms. 16 It is a monovalent organic group having an epoxy group.

[0089] R 15 For example, it may be an alkyl group such as methyl, ethyl, propyl, butyl, isopropyl, isobutyl, tert-butyl, pentyl, hexyl, heptyl, octyl, 2-ethylhexyl, etc.; an alkenyl group such as vinyl, allyl, butenyl, pentenyl, hexenyl, etc.; an aryl group such as phenyl, tolyl, xylyl, naphthyl, biphenyl, etc.; an aralkyl group such as benzyl, phenethyl, etc., etc. 13 Preferred is methyl or phenyl.

[0090] R 16 For example, it may be 2,3-epoxypropyl, 3,4-epoxybutyl, 4,5-epoxypentyl, 2-epoxypropoxyethyl, 3-epoxypropoxypropyl, 4-epoxypropoxybutyl, 2-(3,4-epoxycyclohexyl)ethyl, 3-(3,4-epoxycyclohexyl)propyl, or the like. 16 Preferred is 3-glycidoxypropyl.

[0091] The second siloxane compound may have a plurality of structural units 6. 15 The plurality of R present in the second siloxane compound may be the same as or different from each other. 16 They may be the same as or different from each other. The second siloxane compound may have a repeating unit represented by the above chemical formula (6).

[0092] From the viewpoint of being easy to adjust SI and FI within the above range and being easy to suppress cracks in a molded body formed of the composite, the second siloxane compound is preferably a compound having at least one structural unit selected from the structural unit represented by the following chemical formula (7), the structural unit represented by the following chemical formula (8), the structural unit represented by the following chemical formula (9), and the structural unit represented by the following chemical formula (10). The structural unit represented by the following chemical formula (7) is sometimes referred to as "structural unit 7". The structural unit represented by the following chemical formula (8) is sometimes referred to as "structural unit 8". The structural unit represented by the following chemical formula (9) is sometimes referred to as "structural unit 9". The structural unit represented by the following chemical formula (10) is sometimes referred to as "structural unit 10". The above-mentioned compound having at least one structural unit selected from structural unit 7, structural unit 8, structural unit 9, and structural unit 10 is sometimes referred to as "compound 11". Compound 11 may have all the structural units of structural unit 7, structural unit 8, structural unit 9, and structural unit 10.

[0093] [Chemistry 7]

[0094]

[0095] [Chemistry 8]

[0096]

[0097] [Chemistry 9]

[0098]

[0099] [Chemistry 10]

[0100]

[0101] Compound 11 may have a plurality of structural units 7. Compound 11 may have a repeating unit represented by the above chemical formula (7). Compound 11 may have a plurality of structural units 8. Compound 11 may have a repeating unit represented by the above chemical formula (8). Compound 11 may have a plurality of structural units 9. Compound 11 may have a repeating unit represented by the above chemical formula (9). Compound 11 may have a plurality of structural units 10. Compound 11 may have a repeating unit represented by the above chemical formula (10).

[0102] A commercially available product of Compound 11 may be, for example, AY42-119 manufactured by Dow Corning Toray Corporation.

[0103] The epoxy equivalent of the second siloxane compound may be 500 to 4000, or 1000 to 2500. When the epoxy equivalent is within the above range, the fluidity of the composite is likely to be improved, and the moldability is likely to be improved.

[0104] The softening point of the second siloxane compound is preferably above 40°C and below 120°C, more preferably above 50°C and below 100°C. When the softening point is within the above range, the mechanical strength of the molded body formed by the composite is easily improved. The softening point of the second siloxane compound can be adjusted by the molecular weight, structure (for example, the content ratio of each constituent unit) of the second siloxane compound, the type of organic group bonded to the silicon atom, etc. From the viewpoint of improving the fluidity of the composite, it is preferred to adjust the softening point by the content of the aryl group in the second siloxane compound. The aryl group may be, for example, phenyl, tolyl, xylene, naphthyl, biphenyl, etc. The aryl group is preferably a phenyl group. It is more preferred to adjust the softening point by the content of the phenyl group in the monovalent organic group bonded to the silicon atom in the second siloxane compound. The content of the above phenyl group is preferably adjusted to 60 mol% or more and 100 mol% or less, and more preferably adjusted to 70 mol% or more and 85 mol% or less.

[0105] The weight average molecular weight (Mw) of the second siloxane compound may be 1000 or more and 30000 or less, preferably 2000 or more and 20000 or less, and more preferably 3000 or more and 10000 or less. The weight average molecular weight (Mw) may be measured by gel permeation chromatography (GPC) and may be a value converted using a standard polystyrene calibration curve. The second siloxane compound is preferably a random copolymer.

[0106] The resin composition may contain one or more of the above-mentioned siloxane compounds.

[0107] The content of the siloxane compound in the composite can be 25 parts by mass or more and 45 parts by mass or less, 25 parts by mass or more and 35 parts by mass or less, or 30 parts by mass or more and 35 parts by mass or less, relative to 100 parts by mass of the epoxy resin. When the content of the siloxane compound is within the above range, it is easy to adjust SI and FI within the above range, and it is easy to suppress cracks in a molded body formed from the composite.

[0108] The coupling agent improves the adhesion between the resin composition and the particles containing metal elements constituting the powder containing metal elements, and improves the flexibility and mechanical strength of the molded body formed by the composite. The coupling agent can be, for example, at least one selected from silane compounds (silane coupling agents), titanium compounds, aluminum compounds (aluminum chelates) and aluminum / zirconium compounds. The silane coupling agent can be, for example, at least one selected from epoxy silane, mercapto silane, amino silane, alkyl silane, ureide silane, anhydride silane and vinyl silane. Aminophenyl-based silane coupling agents are particularly preferred. The resin composition can contain one of the above coupling agents, or multiple coupling agents.

[0109] For the environmental safety, recyclability, formability and low cost of the composite, the composite may contain a flame retardant. The flame retardant may be, for example, at least one selected from brominated flame retardants, bulb flame retardants, hydrated metal compound flame retardants, silicone flame retardants, nitrogen-containing compounds, hindered amine compounds, organic metal compounds and aromatic engineering plastics. The resin composition may contain one of the above flame retardants, or may contain multiple flame retardants.

[0110] When a mold is used to form a molded body from a composite, the resin composition may contain wax. The wax functions as a mold release agent while improving the fluidity of the composite during the molding (e.g., transfer molding) of the composite. The wax may be at least one of a fatty acid such as a higher fatty acid and a fatty acid ester.

[0111] The wax may be, for example, at least one of the following: fatty acids such as montanic acid, stearic acid, 12-hydroxystearic acid (Japanese: 12-oxistearic acid), lauric acid, or their esters; fatty acid salts such as zinc stearate, calcium stearate, barium stearate, aluminum stearate, magnesium stearate, calcium laurate, zinc laurate, calcium ricinoleate, 2-ethylhexanoic acid zinc (Japanese: hexanoic acid); stearic acid amide, oleic acid amide, erucic acid amide, behenic acid amide, palmitic acid amide, lauric acid amide, hydroxystearic acid amide, methylene bis stearic acid amide, ethylene bis stearic acid amide, ethylene bis lauric acid amide, distearic acid amide Fatty acid amides such as acyl adipamide, ethylenebisoleamide, dioleyl adipamide, N-stearoyl stearamide, N-oleyl stearamide, N-stearoyl erucamide, hydroxymethyl stearamide, and hydroxymethyl behenamide; fatty acid esters such as butyl stearate; alcohols such as ethylene glycol and stearyl alcohol; polyethers including polyethylene glycol, polypropylene glycol, polytetramethylene glycol and their modified products; polysiloxanes such as silicone oil and silicone lubricating oil; fluorine compounds such as fluorine oil, fluorine lubricating oil, and fluorine-containing resin powder; and waxes such as paraffin wax, polyethylene wax, amide wax, polypropylene wax, ester wax, carnauba wax, and micro wax.

[0112] (Powder containing metal elements)

[0113] The powder containing metal elements (particles containing metal elements) may contain, for example, at least one selected from a metal single substance, an alloy and a metal compound. The powder containing metal elements may contain, for example, at least one selected from a metal single substance, an alloy and a metal compound. The alloy may contain at least one selected from a solid solution, a eutectic and an intermetallic compound. The alloy may be, for example, stainless steel (Fe-Cr alloy, Fe-Ni-Cr alloy, etc.). The metal compound may be, for example, an oxide such as ferrite. The powder containing metal elements may contain one metal element or multiple metal elements. The metal element contained in the powder containing metal elements may be, for example, a base metal element, a noble metal element, a transition metal element or a rare earth element. The composite may contain one metal element-containing powder or may contain multiple metal element-containing powders of different compositions.

[0114] The powder containing metal elements is not limited to the above-mentioned composition. The metal element contained in the powder containing metal elements can be, for example, at least one selected from iron (Fe), copper (Cu), titanium (Ti), manganese (Mn), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), tin (Sn), chromium (Cr), barium (Ba), strontium (Sr), lead (Pb), silver (Ag), praseodymium (Pr), neodymium (Nd), samarium (Sm) and dysprosium (Dy). The powder containing metal elements can also contain elements other than metal elements. The powder containing metal elements can, for example, contain oxygen (О), beryllium (Be), phosphorus (P), boron (B) or silicon (Si). The powder containing metal elements can be a magnetic powder. The powder containing metal elements can be a soft magnetic alloy or a ferromagnetic alloy. The powder containing metal elements may be, for example, a magnetic powder containing at least one selected from Fe-Si alloys, Fe-Si-Al alloys (aluminum silicon iron), Fe-Ni alloys (permalloy), Fe-Cu-Ni alloys (permalloy), Fe-Co alloys (permalloy), Fe-Cr-Si alloys (electromagnetic stainless steel), Nd-Fe-B alloys (rare earth magnets), Sm-Fe-N alloys (rare earth magnets), Al-Ni-Co alloys (aluminum nickel cobalt magnets) and ferrites. Ferrites may be, for example, spinel ferrites, hexagonal ferrites or garnet ferrites. The powder containing metal elements may be a copper alloy such as a Cu-Sn alloy, a Cu-Sn-P alloy, a Cu-Ni alloy or a Cu-Be alloy. The powder containing metal elements may contain one of the above elements and combinations, or may contain multiple of the above elements and combinations.

[0115] The powder containing metal elements may also be a single substance of Fe. The powder containing metal elements may also be an alloy containing iron (Fe alloy). The Fe alloy may be, for example, a Fe-Si-Cr alloy or a Nd-Fe-B alloy. The powder containing metal elements may be at least one of an amorphous iron powder and a carbonyl iron powder. In the case where the powder containing metal elements includes at least one of a single substance of Fe and an Fe alloy, it is easy to make a formed body having a high fill factor and excellent magnetic properties from the composite. The powder containing metal elements may also be an Fe amorphous alloy. As commercially available products of Fe amorphous alloy powder, for example, at least one selected from AW2-08, KUAMET-6B2 (the above are product names manufactured by EPSON ATMIX Co., Ltd.), DAP MS3, DAP MS7, DAP MSA10, DAPPB, DAP PC, DAP MKV49, DAP 410L, DAP 430L, DAP HYB series (the above are product names manufactured by Daido Steel Co., Ltd.), MH45D, MH28D, MH25D and MH20D (the above are product names manufactured by Kobe Steel, Ltd.) can be used.

[0116] <Method for producing composite material>

[0117] In the manufacture of the composite, the powder containing the metal element and the resin composition (constituting the various components of the resin composition) are mixed while being heated. For example, the powder containing the metal element and the resin composition can be mixed while being heated with a kneader, a roller, a stirrer, etc. By heating and mixing the powder containing the metal element and the resin composition, the resin composition is attached to a part or the entire surface of the surface of the particles containing the metal element constituting the powder containing the metal element and covers the particles containing the metal element, and a part or all of the epoxy resin in the resin composition becomes a semi-cured product. As a result, a composite can be obtained. Further wax is added to the powder obtained by heating and mixing the powder containing the metal element and the resin composition, thereby a composite can also be obtained. The resin composition can also be mixed with wax in advance.

[0118] During mixing, the powder containing metal elements, the curing agent such as the siloxane compound, the epoxy resin, the phenolic resin, the curing accelerator and the coupling agent can be mixed in the tank. It is also possible to put the epoxy resin, the curing agent and the curing accelerator into the tank after the powder containing metal elements, the siloxane compound and the coupling agent are put into the tank for mixing and mix the raw materials in the tank. It is also possible to put the curing accelerator into the tank after the siloxane compound, the epoxy resin, the curing agent and the coupling agent are mixed in the tank and further mix the raw materials in the tank. It is also possible to make a mixed powder (resin mixed powder) of the epoxy resin, the curing agent and the curing accelerator in advance, then mix the powder containing metal elements, the siloxane compound and the coupling agent to make a metal mixed powder, and then mix the metal mixed powder and the above-mentioned resin mixed powder.

[0119] The kneading time also depends on the type of kneading machine, the volume of the kneading machine, and the production volume of the composite. For example, it is preferably more than 1 minute, more preferably more than 2 minutes, and more preferably more than 3 minutes. In addition, the kneading time is preferably less than 20 minutes, more preferably less than 15 minutes, and more preferably less than 10 minutes. When the kneading time is less than 1 minute, the kneading is insufficient, the formability of the composite is impaired, and the curing degree of the composite is uneven. When the kneading time is greater than 20 minutes, for example, the curing of the resin composition (such as epoxy resin and phenolic resin) in the groove is promoted, and the fluidity and formability of the composite are easily impaired. When the raw materials in the groove are heated and kneaded with a kneader, the heating temperature, for example, is as long as the semi-cured epoxy resin (epoxy resin of the B stage) is generated and the cured epoxy resin (epoxy resin of the C stage) is inhibited. The heating temperature can be a temperature lower than the activation temperature of the curing accelerator. The heating temperature is, for example, preferably above 50°C, more preferably above 60°C, and more preferably above 70°C. The heating temperature is preferably 150° C. or less, more preferably 120° C. or less, and further preferably 110° C. or less. When the heating temperature is within the above range, the resin composition in the tank softens and easily covers the surface of the metal element-containing particles constituting the metal element-containing powder, and a semi-cured product of the epoxy resin is easily generated, which easily suppresses the complete curing of the epoxy resin during kneading.

[0120] <Molded body>

[0121] The molded body involved in this embodiment may have the above-mentioned composite. The molded body involved in this embodiment may also have a cured product of the above-mentioned composite. The molded body may include at least one selected from an uncured resin composition, a semi-cured product of a resin composition (a resin composition in the B stage) and a cured product of a resin composition (a resin composition in the C stage). The molded body involved in this embodiment can be used as a sealing material for electronic components or electronic circuit substrates. According to this embodiment, cracks in the molded body caused by the difference in thermal expansion coefficient between the metal components of the electronic components or electronic circuit substrates and the molded body (sealing material) can be suppressed.

[0122] <Method for producing molded article>

[0123] The method for manufacturing a molded body according to the present embodiment may include a step of pressurizing the composite in a mold. The method for manufacturing a molded body may include a step of pressurizing the composite covering a part or the entire surface of a metal component in a mold. The method for manufacturing a molded body may include only a step of pressurizing the composite in a mold, or may include other steps in addition to this step. The method for manufacturing a molded body may also include a first step, a second step, and a third step. The details of each step are described below.

[0124] In the first step, a composite is prepared by the above-mentioned method.

[0125] In the second step, a molded body (a molded body of the B stage) is obtained by pressurizing the composite in a mold. In the second step, a molded body (a molded body of the B stage) can be obtained by pressurizing a part or the whole composite covering the surface of the metal component in a mold. In the second step, the resin composition is filled between the particles of each metal element that constitute the powder containing the metal element. Moreover, the resin composition functions as a binding material (adhesive) to bond the particles containing the metal element to each other.

[0126] As a second process, transfer molding of the composite can be implemented. In transfer molding, the composite can be pressurized under the condition of more than 5MPa and less than 50MPa. There is a tendency that the higher the molding pressure, the easier it is to obtain a molded body with excellent mechanical strength. Considering the mass productivity of the molded body and the life of the mold, the molding pressure is preferably more than 8MPa and less than 20MPa. The density of the molded body formed by transfer molding is preferably more than 75% and less than 86% relative to the true density of the composite, and more preferably more than 80% and less than 86%. When the density of the molded body is more than 75% and less than 86%, it is easy to obtain a molded body with excellent mechanical strength. The second process and the third process can be implemented together in transfer molding.

[0127] In the third step, the molded body is cured by heat treatment to obtain a C-stage molded body. The temperature of the heat treatment can be any temperature at which the resin composition in the molded body is fully cured. The temperature of the heat treatment may preferably be above 100°C and below 300°C, more preferably above 110°C and below 250°C. In order to suppress the oxidation of the powder containing metal elements in the molded body, the heat treatment is preferably carried out under an inert atmosphere. When the heat treatment temperature is greater than 300°C, the powder containing metal elements is oxidized by the trace amount of oxygen inevitably contained in the atmosphere of the heat treatment, or the cured resin is deteriorated. In order to fully cure the resin composition while suppressing the oxidation of the powder containing metal elements and the degradation of the cured resin, the holding time of the heat treatment temperature is preferably more than several minutes and less than 10 hours, and may be more preferably more than 3 minutes and less than 8 hours.

[0128] <Electronic components>

[0129] like Figure 2As shown in (a) and (b) in the figure, the electronic components 10a and 10b involved in this embodiment have the above-mentioned cured product 2 of the composite, and the element (device) 3 covered by the cured product 2 of the composite. The element 3 may have a metal component. The element 3 is not particularly limited, and for example, it may be at least one selected from a semiconductor chip, a MEMS (micro-electromechanical system) and a coil. The semiconductor chip is not particularly limited, and may be at least one selected from an IC, an LSI, a system LSI, an SRAM, a DRAM and a flash memory. The metal component possessed by the element 3 may include at least one selected from copper (Cu), gold (Au), silver (Ag) and nickel (Ni). The metal component may be, for example, a coil. The metal component may be an external lead as part of an interposer (lead frame). The metal component may also be an internal lead connecting the element 3 and the external lead. The metal component may also be a bonding wire.

[0130] like Figure 2 As shown in (a) in FIG. 1 , the electronic component 10a may include the above-mentioned cured product 2 of the composite, and the element 5 embedded in the cured product 2 of the composite. In other words, the electronic component 10a may include the element 5, and the cured product 2 of the composite covering the entire element 5. The element 5 may have a metal component. For example, the element 5 may be a coil, and the electronic component 10a may be an inductor, a filter (e.g., an EMI filter), or a transformer.

[0131] like Figure 2 As shown in (b) in FIG. 1 , a portion of the element 3 covered by the composite solidified material 2 may extend outside the composite solidified material 2. In other words, the electronic component 10b may include the element 3 and the composite solidified material 2 partially covering the element 3. The element 3 may include a metal component. For example, the electronic component 10b may be a semiconductor package including an interposer 9 (lead frame), a semiconductor chip 7 disposed on the interposer 9, and a composite solidified material 2 covering the interposer 9 and the semiconductor chip 7, and the external lead as a portion of the interposer 9 may extend outside the composite solidified material 2.

[0132] <Electronic circuit boards>

[0133] like Figure 3As shown, the electronic circuit substrate 100 involved in this embodiment can include a substrate 11 and the above-mentioned electronic component 10a arranged on the surface of the substrate 11. The substrate 11 is not particularly limited, for example, it can be a printed substrate selected from at least one of a rigid substrate, a flexible substrate and a rigid-flexible substrate. The electronic component 10a can be electrically connected to the electronic circuit arranged on the surface of the substrate 11 by, for example, a reflow soldering process. The cured product 2 of the composite possessed by the electronic component 10a is formed by a composite having an SI in the above-mentioned range. Therefore, when the electronic component 10a is heated by the reflow soldering process, cracks caused by the difference in thermal expansion coefficient between the cured product 2 of the composite and the metal member possessed by the element 5 are suppressed.

[0134] Example

[0135] Hereinafter, the present invention will be described in more detail using Examples and Comparative Examples; however, the present invention is not limited to these Examples at all.

[0136] (Example 1)

[0137] [Preparation of composite]

[0138] 100 g of biphenylene aralkyl epoxy resin, 38.7 g of phenol novolac resin (curing agent), 2.0 g of curing accelerator and 7.0 g of montanic acid ester (wax) were put into a plastic container (Japanese: ポリContainer). These raw materials were mixed in the plastic container for 10 minutes to prepare a resin mixture. The resin mixture corresponds to all other components in the resin composition except the compound having a siloxane bond and the coupling agent.

[0139] As the biphenylene aralkyl type epoxy resin, NC-3000 manufactured by Nippon Kayaku Co., Ltd. was used.

[0140] As the phenol novolac resin, HP-850N manufactured by Hitachi Chemical Co., Ltd. was used.

[0141] As a curing accelerator, 2-ethyl-4-methylimidazole (2E4MZ) manufactured by Shikoku Chemicals Co., Ltd. was used.

[0142] As the montanic acid ester, LICOWAX-E manufactured by Clariant Chemicals Co., Ltd. was used.

[0143] Amorphous iron powder 1 and amorphous iron powder 2 were uniformly mixed for 5 minutes with a pressurized biaxial kneader (manufactured by Japan Spindle Manufacturing Co., Ltd., capacity 5L) to prepare 3835g of powder containing metal elements. The content of amorphous iron powder 1 in the powder containing metal elements was 75% by mass. The content of amorphous iron powder 2 in the powder containing metal elements was 25% by mass. 3.0g of 3-glycidoxypropyltrimethoxysilane (coupling agent) and 30g of caprolactone-modified dimethyl silicone (compound with siloxane bond) were added to the powder containing metal elements in the biaxial kneader. Then, the contents of the biaxial kneader were heated to 90°C, and the contents of the biaxial kneader were mixed for 10 minutes while maintaining the temperature. Then, the above-mentioned resin mixture was added to the contents of the biaxial kneader, and the contents were melted and kneaded for 15 minutes while the temperature of the contents was maintained at 120°C. After the kneaded product obtained by the above melting and kneading is cooled to room temperature, the kneaded product is crushed with a hammer until the kneaded product has a predetermined particle size. It should be noted that the above-mentioned "melting" means that at least a portion of the resin composition in the content of the biaxial kneader is melted. The powder containing the metal element in the composite is not melted during the preparation process of the composite.

[0144] As the amorphous iron powder 1 , 9A4-II (average particle size: 24 μm) manufactured by EPSON ATMIX Corporation was used.

[0145] As the amorphous iron powder 2 , AW2-08 (average particle size: 5.3 μm) manufactured by EPSON ATMIX Corporation was used.

[0146] As 3-glycidoxypropyltrimethoxysilane, KBM-403 manufactured by Shin-Etsu Chemical Co., Ltd. was used.

[0147] As the caprolactone-modified dimethyl silicone, DBL-C32 manufactured by Gelest Co., Ltd. was used. The caprolactone-modified dimethyl silicone is a compound represented by the above-mentioned chemical formula (3).

[0148] The above method was used to prepare the composite of Example 1. The content of the powder containing the metal element in the composite was 95.5% by mass.

[0149] [Evaluation of liquidity]

[0150] 50g of the compound of Example 1 was placed in a transfer tester, and the spiral flow momentum (unit: mm) of the compound was measured under the conditions of a mold temperature (molding temperature) of 140°C, an injection pressure of 13.5MPa, and a molding time of 360 seconds. The spiral flow momentum refers to the length of the softened or liquefied compound flowing in the spiral curve (Archimedes spiral)-shaped groove formed in the above-mentioned mold. That is, the spiral flow momentum refers to the flow distance of the softened or liquefied compound. The easier the compound softened or liquefied by heating flows, the greater the spiral flow momentum. That is, the spiral flow momentum of a compound with excellent fluidity is large. As a transfer tester, a transfer molding machine manufactured by T-Marushichi Co., Ltd. was used. As a mold, a mold for spiral flow measurement based on ASTM D3123 was used. The spiral flow momentum of Example 1 is shown in Table 2 below.

[0151] [Bending test]

[0152] By transfer molding of the composite of Example 1 at 140°C, Figure 1 Test piece 1 shown. Test piece 1 is a rectangular parallelepiped (rod) containing a cured product of the composite. The pressure applied to the composite is 13.5 MPa. The dimensions of test piece 1 are longitudinal width L: 80 mm × transverse width W: 10 mm × thickness t: 3.0 mm. Using an automatic plotter with a constant temperature bath, a three-point support type bending test was performed on test piece 1. As the automatic plotter, AGS-500A manufactured by Shimadzu Corporation was used. The temperature of the constant temperature bath is 250°C. As Figure 1 As shown, in the bending test, two fulcrums are used to support one surface of the test piece 1. A load is applied to the center position between the two fulcrums on the other surface of the test piece 1. The load when the test piece 1 is broken and the deflection (elongation) of the test piece 1 just before the test piece 1 is broken are measured. The measurement conditions of the bending test are shown below.

[0153] Distance between two supporting points Lv: 64.0±0.5mm

[0154] Head speed: 2.0±0.2mm / min

[0155] Recording paper speed: 100mm / min

[0156] Recording paper full scale (Japanese: チャートフルスケール): 490N (50kgf)

[0157] Based on the following formula (A), the bending strength σ (unit: MPa) is calculated. Based on the following formula (B), the bending elastic modulus E (unit: GPa) is calculated. Based on the following formula (C), the bending elongation ε (unit: %) is calculated. In the following formula, "P" is the load when the test piece 1 is destroyed (unit: N). "Lv" is the distance between the two fulcrums (unit: mm). "W" is the lateral width of the test piece 1 (unit: mm). "t" is the thickness of the test piece 1 (unit: mm). "F / Y" is the slope of the straight line portion of the load-deflection curve (unit: N / mm). "s" is the deflection of the test piece 1 just before the test piece 1 is destroyed (unit: mm). σ, E and ε of Example 1 are shown in Table 2 below.

[0158] σ=(3×P×Lv) / (2×W×t 2 ) (A)

[0159] E=[Lv 3 / (4×W×t 3 )]×(F / Y) (B)

[0160] ε=(600×s×t) / Lv 2 (C)

[0161] [Calculation of fracture index FI]

[0162] The fracture index FI (unit: MPa) was calculated based on the following formula (II) using the results of the bending test. The FI of Example 1 is shown in Table 2 below.

[0163] FI=ε×σ / 2(II)

[0164] [Thermomechanical analysis]

[0165] The composite of Example 1 was subjected to a thermomechanical analysis (TMA). In TMA, the composite of Example 1 was formed under the conditions of 140°C, 360 seconds, and 13.5 MPa, and the formed body of the composite was cured at 180°C for 2 hours to prepare a test piece (cured composite). In TMA, the test piece was heated from room temperature (25°C) to 250°C. The load applied to the test piece in TMA was 10g. The heating rate was 5°C / minute. Based on the results of TMA, the glass transition temperature Tg (unit: °C) of the cured composite, the thermal expansion coefficient CTE1 (unit: ppm / °C) of the cured composite when it was above 25°C and below Tg°C, and the thermal expansion coefficient CTE2 (unit: ppm / °C) of the cured composite when it was above Tg°C and below 250°C were determined. Tg, CTE1, and CTE2 of Example 1 are shown in Table 2 below.

[0166] [Calculation of expansion difference D]

[0167] Using the results of the thermomechanical analysis, the expansion difference D between the cured product of the composite of Example 1 and copper at 25° C. to 250° C. was calculated based on the following formula (III). D of Example 1 is shown in Table 2 below.

[0168] D=CTE1×(Tg-25)+CTE2×(250-Tg)-17×(250-25) (III)

[0169] [Calculation of stress index SI]

[0170] The stress index SI was calculated based on the following formula (I) using the results of the bending test and the thermomechanical analysis. The SI of Example 1 is shown in the following Table 1. SI is equal to D×E / σ.

[0171] SI=|[CTE1×(Tg-25)+CTE2×(250-Tg)-17×(250-25)]×E / σ|(I)

[0172] [Reflow treatment]

[0173] By transfer molding, a copper metal component is sealed with the composite of Example 1, and the composite is cured to obtain a molded body. The molded body is subjected to a reflow soldering treatment. The maximum heating temperature in the reflow soldering treatment is 260°C. The heating time is 300 seconds. After the reflow soldering treatment, the molded body is observed, and the presence or absence of cracks in the molded body of Example 1 is investigated. The results of the reflow soldering treatment of Example 1 are shown in Table 2 below. "A" recorded in the following table means that no cracks are formed in the molded body. "B" means that cracks are formed in the molded body.

[0174] (Examples 2 to 6)

[0175] In Examples 2 to 6, the compositions shown in Table 1 below were used as raw materials for the composites. The mass (unit: g) of each composition used in Examples 2 to 6 is the value shown in Table 1 below. Except for these matters, the composites of Examples 2 to 6 were prepared in the same manner as in Example 1. Measurements and evaluations related to the composites of Examples 2 to 6 were performed in the same manner as in Example 1. The results of the measurements and evaluations of Examples 2 to 6 are shown in Table 2 below.

[0176] (Comparative Example 1)

[0177] In Comparative Example 1, the composition shown in Table 1 below was used as a raw material of the composite. The mass (unit: g) of each composition used in Comparative Example 1 is the value shown in Table 1 below. Except for these matters, the composite of Comparative Example 1 was prepared by the same method as Example 1. The measurement and evaluation related to the composite of Comparative Example 1 were performed by the same method as Example 1. The results of the measurement and evaluation of Comparative Example 1 are shown in Table 2 below.

[0178] AER-4001 described in the following table is an isocyanate-modified epoxy resin manufactured by Asahi Kasei Corporation (formerly Asahi Kasei Electronic Materials Corporation).

[0179] MEHC-7851SS described in the following table is a biphenylene aralkyl type phenol resin (curing agent) manufactured by Meiwa Chemicals Co., Ltd.

[0180] C11Z described in the following table is 2-undecylimidazole (curing accelerator) manufactured by Shikoku Chemical Industry Co., Ltd.

[0181]

[0182]

[0183] Industrial Applicability

[0184] The composite according to the present invention can suppress cracks in a molded body made of the composite and a metal member, and therefore has high industrial value.

[0185] Explanation of symbols

[0186] 1 ... test piece, 2 ... cured compound, 3, 5 ... element, 7 ... semiconductor chip, 9 ... interposer, 10a, 10b ... electronic component, 11 ... substrate, 100 ... electronic circuit substrate, P ... load, Lv ... distance between supporting points, L ... longitudinal width of the test piece, W ... lateral width of the test piece, t ... thickness of the test piece.

Claims

1. A composite material comprising a powder containing a metal element and a resin composition, The powder containing the metal element is at least one of a single substance of iron and an alloy containing iron. Furthermore, the powder containing metal elements is a soft magnetic powder. The content of the powder containing the metal element is 94 mass % or more and less than 100 mass %, The resin composition contains an epoxy resin, a curing agent and a compound having a siloxane bond. The compound having a siloxane bond has a structural unit represented by the following chemical formula (1) and a structural unit represented by the following chemical formula (2), In the chemical formula (1), R 1 and R 2 are each independently an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, a monovalent organic group having an epoxy group, a monovalent organic group having a carboxyl group, or a polyalkylene ether group having 3 to 500 carbon atoms, In the chemical formula (2), R 3 is an alkylene group having 1 to 10 carbon atoms, The glass transition temperature of the cured product of the composite is expressed as Tg°C. The thermal expansion coefficient of the cured product of the composite at 25°C or higher and lower than Tg°C is represented by CTE1. The thermal expansion coefficient of the cured product of the composite at a temperature of not less than Tg°C and not more than 250°C is represented by CTE2. The bending elastic modulus of the cured product of the composite at 250° C. is represented by E. The flexural strength of the cured product of the composite at 250°C is denoted as σ. in, The units of CTE1 and CTE2 are ppm / °C, the unit of E is GPa, and the unit of σ is MPa. The stress index SI of the cured product of the composite material defined by the following formula (I) is greater than or equal to 0 and less than or equal to 150, SI=|[CTE1×(Tg-25)+CTE2×(250-Tg)-17×(250-25)]×E / σ| (I).

2. The composite according to claim 1, wherein The bending elongation of the cured product of the composite at 250°C is expressed as ε, and the unit of ε is %. The fracture index FI defined by the following formula (II) is 3.0 MPa or more and 10.0 MPa or less, FI=ε×σ / 2(II) 3 . A molded body comprising a cured product of the composite according to claim 1 or 2 .

4. An electronic component comprising a cured product of the composite material according to claim 1 or 2, and an element covered with the cured product of the composite material, The element has a metal component.

Citation Information

Patent Citations

  • inductor

    JP2014013803A

  • Epoxy resin composition for sealing semiconductor and semiconductor manufacturing method

    CN107400334A

  • Encapsulating liquid epoxy resin composition, electronic component device including element encapsulated with the encapsulating liquid epoxy resin composition, and wafer level chip size package

    JP2010138384A

  • RESIN COMPOUND FOR Nd-Fe-B BASED BOND MAGNET, Nd-Fe-B BASED BOND MAGNET, AND MANUFACTURING METHOD THEREOF

    JP2017034097A